2013
DOI: 10.1038/ejhg.2013.199
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of dyslexia candidate genes in the European cross-linguistic NeuroDys cohort

Abstract: Dyslexia is one of the most common childhood disorders with a prevalence of around 5-10% in school-age children. Although an important genetic component is known to have a role in the aetiology of dyslexia, we are far from understanding the molecular mechanisms leading to the disorder. Several candidate genes have been implicated in dyslexia, including DYX1C1, DCDC2, KIAA0319, and the MRPL19/C2ORF3 locus, each with reports of both positive and no replications. We generated a European cross-linguistic sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 49 publications
3
50
0
5
Order By: Relevance
“…Although putative effects for individual variants have on occasion been replicated, many nonreplications in well-powered samples have been reported. In recent meta-analyses, the relationship between language/reading phenotypes and candidate variants has often remained equivocal (15). Some of the original Exome sequencing has also been performed on five members of an isolated island population with a high incidence of SLI (188).…”
Section: Linkage Studies Of Common Language-related Disordersmentioning
confidence: 99%
“…Although putative effects for individual variants have on occasion been replicated, many nonreplications in well-powered samples have been reported. In recent meta-analyses, the relationship between language/reading phenotypes and candidate variants has often remained equivocal (15). Some of the original Exome sequencing has also been performed on five members of an isolated island population with a high incidence of SLI (188).…”
Section: Linkage Studies Of Common Language-related Disordersmentioning
confidence: 99%
“…or to apply only to a specific population [48]. Meanwhile, we do have much simpler behavioural, familial and environmental measures that do a pretty good job of identifying young children at risk for reading difficulties [49,50].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Variant has been, at least nominally, replicated as genetic risk factor in German-and English-speaking individuals (Dahdouh et al, 2009;Wigg et al, 2004). This genetic variant was also reported in a metaanalysis of dyslexic individuals from Austria, France, Germany, Switzerland, and the Netherlands (Becker et al, 2014), and was found in association with reading in non-affected individuals (Bates et al, 2010). On chromosomal region DYX2, the dyslexia-associated genes DCDC2 and KIAA0319 have been consistently replicated in different languages: A large deletion in DCDC2-rs71745442 was reported as genetic risk factor in German-, English-, and Italian-speaking participants with dyslexia Marino et al, 2012;Meng et al, 2005;Wilcke et al 2009), while variant KIAA0319-rs6935076 was confirmed as a risk factor in numerous studies on reading abilities in unaffected and dyslexic populations (Cope et al, 2005;Couto et al, 2010;Luciano et al, 2007;Newbury et al, 2011; M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 6 2008; Scerri et al, 2011).…”
Section: A N U S C R I P Tmentioning
confidence: 79%